Autimatic tools of match analysis : inspecting soccer team's dispersion - Manuel Clemente, Filipe (2012)
The contracting-expanding soccer teams' relationship is one of the most important dynamic behaviors of the game. Therefore, a soccer game was analyzed using the centroid and stretch index method, while recording the team's ball possession status (with or without ball possession). The correlation test suggest an inverse relationship between opposing teams (r _(1508)=- 0.054) during all game. When considering ball possession by the teams, the results of the stretch index confirm that there are statistical differences with a small effect between the moments with and without possession of the ball for team B (F_(1; 1506)=22.777; p-value≤0.001; η^2=0.015; Power=0.998). Therefore, it was possible to confirm that the contracting -expanding relationship is an intrinsic behaviour of a soccer game in relation to ball possession.